The 10 Predicaments of Maui. Notes on Tricksters - Robertson, N (Clouds, Artspace, 2008)
A 7000 word essay The 10 Predicaments of Maui.Notes on Tricksters. A response to the Francis Alys exhibition (to be continued) 1992- at Artspace, Auckland 2005 on the role of the Trickster and contemporary art.
Keywords: Art; Trickster; Francis Alys; Maui; Maori